Actinobacterial‐mediated synthesis of silver nanoparticles and their activity against pathogenic bacteria. Issue 3 (8th September 2016) - Wypij, Magdalena; Golinska, Patrycja; Dahm, Hanna; Rai, Mahendra
Abstract : In this study, silver nanoparticles (AgNPs) were biosynthesised by using acidophilic actinobacterial SH11 strain isolated from pine forest soil. Isolate SH11 was identified based on 16S rRNA gene sequence to Streptomyces kasugaensis M338‐M1 T and S . celluloflavus NRRL B‐2493 T (99.8% similarity, both). Biosynthesised AgNPs were analysed by UV–visible spectroscopy, which revealed specific peak at λ  = 420 nm. Transmission electron microscopy analyses showed polydispersed, spherical nanoparticles with a mean size of 13.2 nm, while Fourier transform infrared spectroscopy confirmed the presence of proteins as the capping agents over the surface of AgNPs. The zeta potential was found to be −16.6 mV, which indicated stability of AgNPs. The antibacterial activity of AgNPs from SH11 strain against gram‐positive ( Staphylococcus aureus and Bacillus subtilis ) and gram‐negative ( Escherichia coli ) bacteria was estimated using disc diffusion, minimum inhibitory concentration and live/dead analyses. The AgNPs showed the maximum antimicrobial activity against E. coli, followed by B. subtilis and S. aureus . Further, the synergistic effect of AgNPs in combination with commercial antibiotics (kanamycin, ampicillin, tetracycline) was also evaluated against bacterial isolates. The antimicrobial efficacy of antibiotics was found to be enhanced in the presence of AgNPs.